Analisis Beban Kerja Karyawan Banquet Di UNP Hotel And Convention - Aulia Mutia Giska; Hijriyantomi Suyuthie (Lembaga Pengembangan Kinerja Dosen, 2024)
The research purpose is to significantly analyze the workload of banquet employees at UNP Hotel & Convention. The research approach is descriptive qualitative. Interviews, observations and documentation were used for the process of data collection. There were 6 respondents from UNP Hotel & Convention banquet employees. Triangulation of data and methods by interview reduction were used to the data analyzed. The research results shown that the workload of banquet employees is not maximal. It shown from the working conditions and the use of working time that have not been fully implemented properly according to the established Standard Operating Procedures. Companies can consider increasing the availability of banquet employees to create good performance.